WEED CONTROL WITH ALACHLOR IN IRRIGATED COWPEA (VIGNA UNGUICULATA (L.) WALE) IN A FOREST ZONE OF NIGERIA - AKINYEMIJU, O. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The influence of irrigating different phenological stages on weed control, weed species and density. and cowpea grain yields was investigated in the field in the dry seasons of 1983/84 and !984/85. Results showed that moisture strees, in treatment that were irrigated till the end of the vegetativc phase, led to a reduction in grain yields when compared with treatments that received irrigation till flowering or podding. Weed control by alachlor was inadequate for treatment that received irrigation till the end of vegetative phase only, but adequate for treatments that received irrigation for more than the vegetative phase of growth. There was a good control of Euphorbia heterophylla L., Spigelia anthelmia L. and Amaranthus spinosus L. by alachlor. The potential of sedges being various problem weds under irrigation was observed.